The Evolution of Current Account Deficits in the Euro Area Periphery and the Baltics : Many Paths to the Same Endpoint - Kang, Joong (IMF Working Papers; Working Paper ;, 2013)
Explanations of the large current account deficits for the euro area periphery and the Baltics in the run up to the crisis revolve around two main factors: deteriorating export performance or demand driven booms. We add that there were important movements in transfers and net income balances. While export performance remained relatively stable in most countries, for some countries, when transfers declined, households and firms borrowed so as to maintain the same level of spending. This was part of a persistent failure to adjust to trade deficits, which, along with rising net income payments, led to growing current account deficits. All of these factors played varying roles in the development of current account deficits across these countries.